Factors Influencing Spin-off Activities at Universities: Empirical Evidence from the United Kingdom - Odei, Samuel Amponsah; Stejskal, Jan (Masarykova univerzita, 2018)
This paper intends to develop the understanding of the various factors that contributes to university knowledge transfers and spinoff activities. Using data from the HESA-BCI survey and the Structural Equation Model (SEM) we analysed the various determinants that influence spin off activities of universities in the United Kingdom. The empirical results demonstrate that (1) incentive support provided to academics influences their spin off activities positively; (2) incubation support in the form of science parks, entrepreneurial support, venture capital has a positive influence on universities spin off activities; (3) the governance of universities’ spin off activities doesn’t necessary contribute to academic spin off activities. Practical implications are also offered to universities management, academics and industries on best strategies to support their spin off activities.
Faktory ovlivňující spin-off aktivity na univerzitách: empirická studie z UK
Keywords: Factors; Influencing; Spin-off; Activities; Universities; Empirical; Evidence; from; the; United; Kingdom; Faktory; ovlivňující; spin-off; aktivity; univerzitách; empirická; studie